2011
DOI: 10.1186/1471-2458-11-464
|View full text |Cite
|
Sign up to set email alerts
|

Is proximity to a food retail store associated with diet and BMI in Glasgow, Scotland?

Abstract: BackgroundAccess to healthy food is often seen as a potentially important contributor to diet. Policy documents in many countries suggest that variations in access contribute to inequalities in diet and in health. Some studies, mostly in the USA, have found that proximity to food stores is associated with dietary patterns, body weight and socio-economic differences in diet and obesity, whilst others have found no such relationships. We aim to investigate whether proximity to food retail stores is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 43 publications
1
47
0
1
Order By: Relevance
“…[12][13][14][15][16] Results of this research are equivocal. A review by Beaulac et al 17 found that clear disparities in food access exist by income and race in many municipalities in the United States, but not elsewhere.…”
Section: Introductionmentioning
confidence: 69%
“…[12][13][14][15][16] Results of this research are equivocal. A review by Beaulac et al 17 found that clear disparities in food access exist by income and race in many municipalities in the United States, but not elsewhere.…”
Section: Introductionmentioning
confidence: 69%
“…All 6 resulting models adjusted fully for the following potential confounders: age, sex, marital status, qualification (based on National Vocational Qualification level), ethnicity, time budget, and neighborhood deprivation. Because previous studies have found sex differences in the relationship between food environment exposure and dietary intake (15,(44)(45)(46), the interactions between sex and exposure were included in preliminary analyses, but they were excluded from each of the 6 models because they were not significant (P values ranged from 0.141 to 0.972).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…A large majority of studies have used global regression to model the association between exposure to either healthy or unhealthy food environments and diet-related outcomes (2,3). However, reviews have highlighted the lack of consistency in findings (2, 3), with associations for the same type of relationship being positive (4-10), negative (11), or nonexistent (12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…We used data from the Greater Glasgow Health Board (GGHB) 'Health and Well-Being Survey' (HWB 2002: Jones et al, 2003Macdonald et al, 2011). The HWB sample was stratified proportionately by local authority and deprivation category (DEPCAT), with addresses selected randomly.…”
Section: Datamentioning
confidence: 99%